Factors Influencing Job Satisfaction and Employee Retention at the Export-Import Bank of Thailand - ฤกษ์พินัย ธนธรณ์; อภิบุณโยภาส ปรียานุช; วงศ์จารุพรรณ สิริจินต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to 1) examine the effects of Job Autonomy, Job Mastery, and Job Purpose on Job Satisfaction; 2) investigate their effects on Employee Retention, both directly and through Job Satisfaction as a mediating variable; and 3) analyze the effect of Job Satisfaction on Employee Retention and evaluate its mediating role. The study is grounded in Daniel Pink’s Motivation 3.0 framework, employing a quantitative survey design with a minimum sample of 220 respondents selected via convenience sampling. Data were analyzed using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM), with path coefficients, coefficient of determination (R²), and p-values as key statistical measures. Results indicate that most respondents were female, aged over 44, with more than 20 years of work experience and monthly income between 20,001–40,000 THB. Job Mastery was the only factor with a statistically significant positive effect on Job Satisfaction, while Job Purpose showed a significant effect on Employee Retention and Job Autonomy showed no significant effects. Job Satisfaction did not function as a significant mediator in any pathway. These findings suggest that Job Mastery is a critical driver of both Job Satisfaction and Employee Retention, particularly in organizations with highly structured workflows and standardized operational procedures.